2020
DOI: 10.1521/aeap.2020.32.6.472
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to PrEP Initiation and Adherence Among Transgender and Gender Non-Binary Individuals in Southern California

Abstract: While transgender and gender non-binary (trans/nb) individuals are disproportionately affected by HIV, pre-exposure prophylaxis (PrEP) uptake remains low in this underserved population. We conducted four focus groups with 37 trans/nb individuals in San Diego and Los Angeles to assess barriers and facilitators of PrEP usage. Transcripts were coded for qualitative themes. Although overall PrEP awareness was high, participants reported limited knowledge and misinformation about PrEP. Barriers to PrEP use included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Although depressive symptoms have been identified as barriers to PrEP care [ 49 , 50 ], this review suggests that depressive symptoms alone do not stymie PrEP uptake [ 56 , 58 ]. Indeed, cross-sectional analyses have found depressive symptoms to be positively associated with PrEP use [ 33 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although depressive symptoms have been identified as barriers to PrEP care [ 49 , 50 ], this review suggests that depressive symptoms alone do not stymie PrEP uptake [ 56 , 58 ]. Indeed, cross-sectional analyses have found depressive symptoms to be positively associated with PrEP use [ 33 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in southern CA with 30 TGW found that mental health concerns were identified as barriers to PrEP care [ 48 ]. Similarly, another study conducted in southern CA with 37 individuals, the majority of whom were transgender, identified that mental disorder symptoms made PrEP access difficult [ 49 ]. Similarly, in a study of 25 PrEP users in San Francisco, CA, one participant identified depression-related and HIV-related stigma as a barrier to seeking care [ 50 ].…”
Section: Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our qualitative work found that barriers to PrEP in transgender individuals are multifactorial and include competing health conditions (mental health and substance use), social conditions (housing insecurity and transportation), concerns over interactions with hormones, stigma of taking PrEP, negative health care experiences, and mistrust of providers. 22,23 It is unclear why the intervention was effective for transgender women but not transgender men or nonbinary individuals. Among sex identities, transgender women had the lowest adequate adherence within the iTAB control arm, suggesting they were less adherent than transgender men and nonbinary individuals to begin with.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Even when the medication is covered by insurance, other medical expenses, including copayments, deductibles, and lab costs, may be burdensome, 24 especially among Black and Hispanic/Latino GBMSM. 22,23 The amount of routine out-of-pocket costs that participants were willing to pay varied, and some who were not currently taking PrEP predicted that basic life expenses would prevent them from affording PrEP. Under these circumstances, some questioned the value of a prophylactic medication when there are behavioral alternatives such as condoms or abstinence.…”
Section: Discussionmentioning
confidence: 99%